Experimental and Numerical Studies on Flexural Behavior of GGBS-Based Geopolymer Ferrocement Beams - Taha A. El-Sayed; Ahmed F. Deifalla; Yousry B. Shaheen; Hossam H. Ahmed; Aya K. Youssef (Civil Engineering Journal, 2023)
The ferrocement structural concept has been shown to offer exceptional mechanical properties in terms of toughness, fracture control, and impact resistance, which are achieved by tight spacing and homogeneous reinforcement dispersion within the matrix. The flexure behavior of geopolymer ferrocement beams under axial flexural stress is being explored experimentally and computationally in this present work. Under flexural loads, nine samples of geopolymer ferrocement beams 150 mm thick, 75 mm wide, and 1700 mm long were tested to failure. The reinforcing steel bars and wire meshes, as well as the quantity of wire mesh layers, were the key factors studied. The initial crack load, ultimate failure load, and mid-span deflection with various loading phases, cracking patterns, energy absorption, and ductility index were all studied in relation to the behavior. In terms of carrying capacity, absorbing energy, and ductility, welded steel wire mesh beams fared better than other materials. Using ANSYS-19 software, nonlinear finite element analysis (NLFEA) was carried out to demonstrate the behavior of composite ferrocement geopolymer beams. The ensuing experimental and numerical data demonstrated that the degree of experimental value estimation supplied by the FE simulations was sufficient. It is crucial to demonstrate that, in comparison to control specimens, the increase in strength of specimens reinforced with tensar meshes was reduced by around 15%. Doi: 10.28991/CEJ-2023-09-03-010 Full Text: PDF